The Role of Unemployment Insurance in an Economy with Liquidity Constraints and Moral Hazard - Hansen, Gary D.; Imrohoroğlu, Ayşe (Journal of Political Economy, 1992)
The potential welfare benefits of unemployment insurance, along with the optimal replacement ratio, are studied using a quantitative dynamic general equilibrium model. To provide a role for unemployment insurance, agents in our economy face exogenous idiosyncratic employment shocks and are unable to borrow or insure themselves through private markets. In the absence of moral hazard, replacement ratios as high as .65 are optimal and the welfare benefits of unemployment insurance are quite large. However, if there is moral hazard and the replacement ratio is not set optimally, but is instead set to an empirically plausible value, the economy can be much worse off than it would be without unemployment insurance.